2019
DOI: 10.1002/adtp.201900023
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing CURATE.AI as a Digital Therapeutics Platform by Identifying N‐of‐1 Learning Trajectory Profiles

Abstract: Conventional therapeutic interventions, which range from drug treatment to learning and training regimens, are often given at a fixed dose/intensity. This often leads to sub-optimal responses, or even none at all. Similarly, fixed intensity training can lead to plateaus in learning trajectories and training outcomes. This barrier will impact the field of digital therapeutics, where drug-based therapies may be complemented or replaced by learning and training platforms. A potential solution is to optimize train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

7
0

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 60 publications
0
22
0
Order By: Relevance
“…The CURATE.AI approach is not limited to a clinical setting and unhealthy individuals as shown in a recent study setting a foundation of using CURATE.AI for cognitive training. 86 Below, we discuss CURATE.AI func tionality and versatility based on three prospective use cases. CURATE.AI application for a prospective, singledrug optimization was demonstrated by Zarrinpar et al to man age immunosuppression after liver transplant.…”
Section: What Is It Used For?mentioning
confidence: 99%
“…The CURATE.AI approach is not limited to a clinical setting and unhealthy individuals as shown in a recent study setting a foundation of using CURATE.AI for cognitive training. 86 Below, we discuss CURATE.AI func tionality and versatility based on three prospective use cases. CURATE.AI application for a prospective, singledrug optimization was demonstrated by Zarrinpar et al to man age immunosuppression after liver transplant.…”
Section: What Is It Used For?mentioning
confidence: 99%
“…Subsequent studies resolved this surface, which can rapidly identify optimal combinations, using a second-order algebraic function, with its coefficients determined through a small number of prospective experiments (Abdulla et al, 2020;Al-Shyoukh et al, 2011;Blasiak et al, 2021;Clemens et al, 2019;Ho, 2020;Ho et al, 2020;Lee et al, 2017;Lim et al, 2020;Mohd Abdul Rashid et al, 2015;Rashid et al, 2018;Silva et al, 2016;Wang et al, 2015;Wong et al, 2008). This correlation has subsequently been verified in prospective, human studies in infectious disease, cancer therapy, transplant medicine, and other indications (Tan BKJ et al, 2021;Blasiak et al, 2020;de Mel et al, 2020;Kee et al, 2019;Pantuck et al, 2018;Shen et al, 2020;Zarrinpar et al, 2016). IDentif.AI does not use pre-existing data for algorithm training, in silico modeling, or synergy prediction.…”
Section: Introductionmentioning
confidence: 91%
“…In this study, dynamic modulation of training intensity on a multi‐tasking software platform revealed major differences between study participants in areas such as performance improvement under high and low intensity training. These N‐of‐1 profiles may serve as a way to optimize the efficacy of digital therapy for a broad array of indications ( Figure ) 5. The promise of digital therapy is already being explored in commercial settings and deployment in established healthcare systems.…”
Section: Harnessing Ai For Digital Therapeuticsmentioning
confidence: 99%